2001
DOI: 10.3109/00207450109149744
|View full text |Cite
|
Sign up to set email alerts
|

Lower Back Pain is Reduced and Range of Motion Increased After Massage Therapy

Abstract: Adults (M age=39.6 years) with low back pain with a duration of at least 6 months received two 30-min massage or relaxation therapy sessions per week for 5 weeks. Participants receiving massage therapy reported experiencing less pain, depression, anxiety and their sleep had improved. They also showed improved trunk and pain flexion performance, and their serotonin and dopamine levels were higher.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
104
1
10

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 211 publications
(123 citation statements)
references
References 27 publications
8
104
1
10
Order By: Relevance
“…In line with the current study, the results of trials (20,21) indicate that massage is effective in reducing pain and functional disability, as well as improving mobility and psychological well-being, in chronic low back pain, especially if accompanied with exercises (20).…”
Section: Discussionsupporting
confidence: 87%
“…In line with the current study, the results of trials (20,21) indicate that massage is effective in reducing pain and functional disability, as well as improving mobility and psychological well-being, in chronic low back pain, especially if accompanied with exercises (20).…”
Section: Discussionsupporting
confidence: 87%
“…Range of motion (ROM) of the lumbar spine is currently the only measure included in popular published guidelines for the assessment of impairment associated with low back pain [3]. As such, measures of ROM are frequently employed as the main objective outcome criterion in quantifying the effects of various treatments for back pain [11,18,23,28,32,51]. Nonetheless, the value of objective measures of spinal mobility in assessing dysfunction and in monitoring changes following treatment remains a highly controversial issue within the spine research community.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies demonstrated that massage can modulate pain and increase range of motion [22,23]. It might be appropriate to conduct preperformance massage for athletes with pain or athletes who require greater range of motion to achieve better performance.…”
Section: Discussionmentioning
confidence: 99%